Using Group Peer-Teaching to Enhance Students’ Motivation and Engagement - Andreas Winardi (UICELL, 2022)
Motivation and Engagement are two components for successful learning. It is difficult to achieve learning objectives when the students are not motivated and less engaged in the teaching-learning activities. Hence, the research aimed to investigate whether group peer-teaching can be an alternative method to boost students’ motivation and engagement. 32 students of a private university in Yogyakarta taking English for Specific Purposes (ESP) Vocabulary class participated in the research. They were divided into four groups consisted of eight students. Each group was asked to teach their classmates using Academic Word Lists as their teaching materials. The researched employed observations and interviews as the instruments for data collection. Then the data was analyzed qualitatively. The result of the research showed that group peer-teaching was quite effective in building students’ motivation and increasing their engagement. Keywords: Peer-Teaching, Motivation, Engagement